Durbar High School’s Contribution to the Educational History of Nepal - Nembang, Rama Nembang (HISAN: Journal of History Association of Nepal, 2025)
is study provides a compressive historical significance and status of Durbar High School, in the educational history of Nepal. Nepal’s first formal modern educational institution, established in 1854 AD by Janga Bahadur Rana. Initially founded by the Rana regime to provided English education to their children, Durbar High School played a pioneering role in introducing modern education on the country. Over time it became a symbol of educational reform opening its doors to the broader public and producing numerous distinguished personalities, including administrator, politicians, intellectuals and professionals who contributed significantly to the nation’s development. The school’s historical importance is underscored by its role in the early propagation of education during a time when much of Nepal remained isolated from formal learning. It paved the way for the development of the education system in Nepal, contributing to the emergence of a modern state. Despite its remarkable contributions, the school has experienced significant challenges throughout its history. The curriculum during the Rana period, which was designed and imported from India, was not well-suited to the local context and the school’s exclusivity limited its brooded impact. In recent decades, Durbar High School has faced further challenge, including a decline in academic standards, infrastural decay and competition from emerging private schools. The 2015 AD earthquake severely damaged the school’s facilities, but its subsequent reconstruction, with support from the Chinese government, has revitalized it’s in fracture. This restoration has led to increased student enrollment and renewed interest in the school, giving it a new opportunity to regain its prominence. Durbar High School is the first formal educational institution in the country to spread the light of modern education among the general public for decades, peacefully and steadily even during the Rana regime.